2014
DOI: 10.1007/s10654-014-9947-7
|View full text |Cite
|
Sign up to set email alerts
|

Recalibration of the SCORE risk chart for the Russian population

Abstract: Persisting high levels of cardiovascular mortality in Russia present a specific case among developed countries. Application of cardiovascular risk prediction models holds great potential for primary prevention in this country. Using a unique set of cohort follow-up data from Moscow and Saint Petersburg, this study aims to test and recalibrate the Systematic Coronary Risk Evaluation (SCORE) methods for predicting CVD mortality risks in the general population. The study is based on pooled epidemiological cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…We assessed a hypothetical impact of the reduction in male smoking on deaths from CVD in 2008-2016. The estimation procedure was based on data that have been used in our earlier estimation of the risk of CVD death in Russia associated with current smoking [24]. We used a proportional hazard model to calculate separate hazard ratios for the three ranges of ages at baseline: 15 to 49, 50 to 64, and 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…We assessed a hypothetical impact of the reduction in male smoking on deaths from CVD in 2008-2016. The estimation procedure was based on data that have been used in our earlier estimation of the risk of CVD death in Russia associated with current smoking [24]. We used a proportional hazard model to calculate separate hazard ratios for the three ranges of ages at baseline: 15 to 49, 50 to 64, and 65 and older.…”
Section: Discussionmentioning
confidence: 99%
“…The calibration of the SCORE model was different among various populations. Sometimes it performed well, 26,27 although other studies in Europe, 24 and Russia 28 showed a degree of under-or overestimation. External validity depends on the truth of the regression coefficients, the distribution of the predictors, and the baseline CVD free survival.…”
Section: Discussionmentioning
confidence: 85%
“…The main aspects of design and research methods are published previously [7,8]. 1,200 patients with dierent values of the cardiovascular risk, calculated on the scale of SCORE (Systematic Coronary Risk Evaluation), were included in the study [9]. The subgroup 1 patients with low to moderate risk of cardiovascular events (< 5%), the subgroup 2 patients without clinic of coronary heart disease (CHD), but with high and very high risk of cardiovascular events (≥ 5%), the subgroup 3 patients with ischemic heart disease (angina, myocardial infarction, revascularization).…”
Section: Methodsmentioning
confidence: 99%